Speech Intelligibility of Lecture Theatres in Obafemi Awolowo University, Ile-Ife, Nigeria - Osasona, Oladipo; Fisusi, Abimbola A.; Osasona, C.O.; Onabanjo, B.O.; Yesufu, Thomas K. (Ife Journal of Technology, 2011)
This work measured the speech intelligibility of lecture theatres in Obafemi Awolowo University (OAU), Ile-Ife, Nigeria using the Rapid Speech Transmission Index (RASTI) and Speech Transmission Index for Public Address (STIPA) methods. These methods are objective speech intelligibility measurement methods and they have been used in this work to determine definite and quantitative speech intelligibility values of lecture theatres in OAU unavailable before. RASTI is known to overestimate values when public address systems are involved and this was also observed to be true in this work. STIPA values are therefore recommended for making decisions related to speech intelligibility of the lecture theatres while RASTI values were evaluated for record purposes. Lecture theatres with architectural designs that minimize reverberation in addition to good interior acoustic enhancements were observed to have higher RASTI and STIPA values than lecture theatres with poor architectural design and poor acoustic enhancements.